The Impact of Energy on Global Economy - Safa, Henri (International Journal of Energy Economics and Policy, 2017)
The paper displays and explicit the interrelation that can be found between energy and economy. While energy is essential for human development, squandering should be prevented to avoid detrimental feedback from global warming. A better use of energy may enhance energy intensity but energy efficiency gains are hard to implement and slow. In order to evaluate the impact of energy on global economy, instead of using the usual statistical methods, we suggest an approach based on the production cost of products. Each activity sector is analyzed regarding its energy needs and related costs. The methodology has been applied to the case of France. It is found that energy affects over 60% of the global economy in France. Keywords: Energy impact, GDP, Economy, Energy transition JEL Classifications: Q4, Q43